Um olhar crítico-libertador sobre o movimento de construção curricular da rede municipal de Sorocaba entre 1999 e 2007 - Nunes, Fabiana Boschetti (Universidade Federal de São Carlos, 2018)
The present research deals with the movement of curricular construction of the municipal network of Sorocaba between the years 1999 and 2007, with the objective of investigating the approximations and distances of this one with Paulo Freire's conception of critical-liberating curriculum. It presents a qualitative approach and makes use of bibliographical and documentary research to find the results. The main theoretical bases were: Paulo Freire, Moisey Mikhaylovich Pistrak, Luiz Carlos de Freitas, Antonio Flavio Barbosa Moreira, Thomaz Tadeu da Silva, Ivor F. Goodson, Antonio Fernando Gouvêa da Silva, Ana Maria Saul, Alice Cassimiro Lopes, Demétrio Delizoicov, among others. In the preliminary analyzes, we observed an apparent approximation of the Sorocaba curriculum with the Freirean curriculum perspective, when we find the texts of Paulo Freire, the readings of the innovative experiences coming from the municipalities and the technical staff of the Paulo Freire Institute (IPF, 1998 - like the Citizen School of Porto Alegre). Among the results of the curricular movement of this municipality in constructing a curriculum concerned with the local reality and its articulations with the school knowledge, initially, we observed that this curriculum sought to break the logic of the linear content, of the sequences of contents designated by didactic books, understanding that the specific concepts of the areas of knowledge are not an end in itself, given that such a concept, in a critical-liberating perspective, should be in the service of a social practice. We explain that this curricular proposal, once analyzed based on the curricular theories, went through the three (traditional, critical and post-critical) and also identified the presence of the freirean categories addressed: dialogue, problematization of reality and praxis implicitly, without deepening or distant from conception in Freire, because at that time, the organization of teaching through thematic complexes was mistakenly seen in relation to the generative themes proposed by Paulo Freire.
Keywords: Teorias do currículo, Currículo crítico-libertador, Paulo Freire, Complexo Temático, Pistrak.; Theories of the curriculum, Critical-liberating curriculum, Paulo Freire, Thematic Complex, Pistrak.; CIENCIAS HUMANAS::EDUCACAO::CURRICULO::CURRICULOS ESPECIFICOS PARA NIVEIS E TIPOS DE EDUCACAO